Philosophical Dimensions in Ai Qing’s 1978 Poems: A Study of “Umbrella, Hope, Mirror, and Fish Fossil” - Mayke Ruth Loyali; Nurni Wahyu Wuryandari (Sinolingua: Journal of Chinese Studies, 2025)
Ai Qing (1910–1996) is one of China’s most celebrated poets, renowned for his deceptively simple yet deeply philosophical verses that resonate with everyday life. His poetic career was interrupted for over two decades due to China’s turbulent political and social upheavals, culminating in his return to literary prominence in 1978. This period marked a stylistic evolution, as scholars have noted, wherein his works increasingly employed symbolism—such as Umbrella, Hope, Mirror, and Fish Fossil—to convey existential reflections.‌ The study concludes that the four Ai Qing poems selected as the corpus employ figurative language—primarily ‌personification‌ and ‌symbolization‌ of everyday objects—to convey profound philosophical messages. These works advocate for: Altruism‌ (being beneficial to others), Resilience‌ (remaining hopeful in adversity), Truth-seeking‌ (expressing reality unflinchingly), and Self-discovery‌ (continuously exploring one’s potential). This aligns with Ai Qing’s 1978 poetic resurgence, where his style evolved to blend simplicity with existential depth, using objects like Mirrors and Fish Fossils as metaphors.